Classical Conceptions of Moral Education: A Comparative Analysis of Al-Ghazali’s Tazkiyatun Nafs and Ibnu Miskawaih’s Tahdzib al-Akhlaq and Their Relevance to the Contemporary Youth Moral Crisis - Armalena Armalena; Ali Amran; Erman Erman; Tamrin Kamal; Firdaus Firdaus (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2026)
Adolescence in the current digital era is confronting a complex moral crisis and value disorientation, manifested in phenomena such as cyber-bullying, hedonism, and identity insecurity. This research aims to reconstruct a holistic moral education model by synthesizing the classical insights of Al-Ghazali and Ibnu Miskawaih. The methodology employed is qualitative library research with a comparative-philosophical approach toward the concepts of Tazkiyatun Nafs (Purification of the Soul) and Tahdzib al-Akhlaq (Refinement of Character). The findings indicate that Al-Ghazali emphasizes a "bottom-up" spiritual transformation through heart purification to achieve divine proximity, whereas Ibnu Miskawaih underscores a "top-down" rational habituation through moderation to achieve social well-being. The novelty of this research lies in the formulation of the "Spiritual-Rational Moral Dialectics" model, where spirituality functions as the depth of internal meaning and rationality serves as the logical structure for action to ensure ethical consistency. This study concludes that effective moral education requires a synergy between inner spiritual resilience and critical reasoning. Reliance solely on spiritual aspects risks social detachment, while an exclusive focus on rationality may produce individuals lacking in empathy. This integrative model offers a strategic navigation tool for educators and counselors to foster a generation possessing both spiritual clarity and intellectual acumen, ensuring the sustainability of a dignified civilization amidst massive technological disruption.Keyword:Al-Ghazali; Ibnu Miskawaih; Tazkiyatun Nafs; Tahdzib al-Akhlaq; Moral EducationDigital Era.